2015
DOI: 10.1158/1055-9965.epi-14-0926
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tailored Risk Communications for Skin Cancer Prevention and Detection: The PennSCAPE Randomized Trial

Abstract: Background Prevention and early detection measures for melanoma, such as sun avoidance and skin examinations, are important, but are practiced inconsistently. In this replication of the Project SCAPE trial, we sought to determine whether tailored print materials were more effective at improving adherence than generic print materials for patients at increased-risk of skin cancer. Methods Participants were randomized to receive personalized mailed communications about their skin cancer risk and recommended sun… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
61
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(63 citation statements)
references
References 25 publications
(33 reference statements)
1
61
0
Order By: Relevance
“…Four studies assessed sun‐related attitudes, of which three found significant differences in the sun risk attitude and perceived sun damage susceptibility . Sixteen studies found a significant protective behavioural changes and two studies reported significant changes in the intention to change sun protection behaviour …”
Section: Resultsmentioning
confidence: 99%
“…Four studies assessed sun‐related attitudes, of which three found significant differences in the sun risk attitude and perceived sun damage susceptibility . Sixteen studies found a significant protective behavioural changes and two studies reported significant changes in the intention to change sun protection behaviour …”
Section: Resultsmentioning
confidence: 99%
“…Self-reported sunscreen use is also used as one way of evaluating the efficacy of public health campaigns aimed at increasing sun avoidance behaviors and preventing skin cancer (Buller et al 2015; Glanz et al 2015; Youl et al 2015). It is therefore important to understand the validity of self-reported frequency of sunscreen use.…”
Section: Introductionmentioning
confidence: 99%
“…Yet the predominant self-report assessments for sun protection (Centers for Disease Control and Prevention, 2007) are not designed to assess consistency of sun protection, as they direct respondents to generate a cumulative frequency over a broad time period (e.g., “sometimes” or “most of the time” using sunscreen while outside on a sunny day last summer). Using these global self-report methods, it appears that individuals with a family history of melanoma use sun protection inconsistently (Azzarello, Dessureault, & Jacobsen, 2006; Bishop et al, 2007; Geller et al, 2006), and even well-designed, personalized interventions do not resolve this inconsistency (Azzarello et al, 2006; Glanz et al, 2015; Manne et al, 2010). For example, Glanz and colleagues (Glanz et al, 2015) examined the influence of tailored risk information on sun protection among individuals at risk of melanoma and found that while sunscreen use increased significantly in the intervention group, that substantial inconsistency remained.…”
Section: Introductionmentioning
confidence: 99%
“…Using these global self-report methods, it appears that individuals with a family history of melanoma use sun protection inconsistently (Azzarello, Dessureault, & Jacobsen, 2006; Bishop et al, 2007; Geller et al, 2006), and even well-designed, personalized interventions do not resolve this inconsistency (Azzarello et al, 2006; Glanz et al, 2015; Manne et al, 2010). For example, Glanz and colleagues (Glanz et al, 2015) examined the influence of tailored risk information on sun protection among individuals at risk of melanoma and found that while sunscreen use increased significantly in the intervention group, that substantial inconsistency remained. Understanding the decisions that lead to sun protection use is critical to the development of interventions to address pervasive inconsistency in these behaviors.…”
Section: Introductionmentioning
confidence: 99%